Order from chaos. - Noy, Natalya (New York ACM, 2005)
Will ontologies help you structure your semi-structured data?
Keywords: Information Systems; Information Storage and Retrieval; Content Analysis and Indexing; Abstracting methods; Software; Software Engineering; Design tools and techniques; Owl; Computing Methodologies; Artificial Intelligence; Knowledge Representation Formalisms and Methods; Semantic networks; Natural language processing; Language parcing and understanding; Document and Text Processing; Document preparation; XML; Design; Human Factors; Languages; Theory